2017
DOI: 10.1002/jez.2110
|View full text |Cite
|
Sign up to set email alerts
|

Repeated immune challenges affect testosterone but not sperm quality

Abstract: Mounting an immunological response is energetically demanding and necessarily redirects allocation of resources toward immune system activation and away from other energetically expensive processes, such as reproduction. Lipopolysaccharide (LPS), a major component of the outer membrane of the cell wall of Gram-negative bacteria Escherichia coli, mimics a bacterial infection without producing the cost of replicating the pathogen and is one of the most commonly used agents to induce an acute phase immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 97 publications
(128 reference statements)
1
3
0
Order By: Relevance
“…They also found that, when faced with an immune challenge through the subcutaneous injection of a lipopolysaccharide (LPS) to stimulate the innate immune system, there was a significant decrease in testosterone levels as well as an increase in cortisol levels. Similar decreases in testosterone levels have been seen after immune challenges in Indian peafowl (Pavo cristatus; Ros et al, 2008), short-tailed fruit bats (Carollia perspicillata; Greiner et al, 2010) and house sparrows (Passer domesticus; Needham et al, 2017). The direction of this effect, of increased immunity causing a decline in testosterone, could be the result of specific chemicals suppressing testosterone or the energetic costs of mounting an immune response may leave less energy to maintain high levels of testosterone (resource allocation constraints; Burness et al, 2010;Demas and Nelson, 2012).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…They also found that, when faced with an immune challenge through the subcutaneous injection of a lipopolysaccharide (LPS) to stimulate the innate immune system, there was a significant decrease in testosterone levels as well as an increase in cortisol levels. Similar decreases in testosterone levels have been seen after immune challenges in Indian peafowl (Pavo cristatus; Ros et al, 2008), short-tailed fruit bats (Carollia perspicillata; Greiner et al, 2010) and house sparrows (Passer domesticus; Needham et al, 2017). The direction of this effect, of increased immunity causing a decline in testosterone, could be the result of specific chemicals suppressing testosterone or the energetic costs of mounting an immune response may leave less energy to maintain high levels of testosterone (resource allocation constraints; Burness et al, 2010;Demas and Nelson, 2012).…”
Section: Introductionsupporting
confidence: 60%
“…Although we found a significant effect of the LPS challenge on circulating testosterone, we did not find an effect on average scrotal volume. Interestingly, Needham et al (2017) found that testosterone levels of house sparrows (P. domesticus) decreased after a first and second LPS challenge, but there was no effect on sperm quality, suggesting that there may be mechanisms in place to avoid consequences of pathogen exposure on reproductive output. The lack of change observed in scrotal size of treated animals in our study may also be due to the acute and short-term effects of the LPS challenge (Lutermann et al, 2012), which may not have been able to change scrotal volume significantly over the relatively short time period.…”
Section: Discussionmentioning
confidence: 99%
“…Negative effects of immune system activation on sperm function have also been seen in great tits Parus major (Losdat et al, 2011) and guppies Poecilia reticulata (Devigili et al, 2017), lending further support to the idea. However, a similar test in the house sparrow Passer domesticus, while demonstrating a negative impact of infection on testosterone, failed to detect harm to sperm quality (Needham et al, 2017). Thus, whether somatic infections negatively impact sperm is likely specific to the host or parasite species, or dependent on the strength of infection.…”
Section: Effects Of Infections In Males Including Stis On Sperm Sucmentioning
confidence: 98%
“…However, such deleterious effects of immunity on male reproductive function are not always observed. For example, a recent study on house sparrows showed no negative effect of immunity on sperm performance despite diminishing testosterone levels (Needham et al, 2017). Because sperm performance is supposedly condition dependent (Simmons and Kotiaho, 2002;Gasparini and Pilastro, 2011), one explanation for our negative result could be that the immune challenge triggered by the experimental infection was not energetically demanding enough to affect individual 'condition' and in turn to impact conditiondependent traits such as sperm performance.…”
Section: Discussionmentioning
confidence: 66%